2007
DOI: 10.1590/s0004-28032007000100011
|View full text |Cite
|
Sign up to set email alerts
|

Doença hepática não-alcoólica: evolução após derivação gastrojejunal em Y-de-Roux pela técnica de fobi-capella

Abstract: RESUMO -Racional -A doença hepática não-alcoólica apresenta alta prevalência entre pacientes com obesidade mórbida, podendo evoluir de esteatose hepática até esteatohepatite e cirrose. Objetivo -Determinar o efeito da derivação gástrica na incidência de doença hepática não-alcoólica e co-morbidades relacionadas em pacientes com obesidade mórbida. Métodos -Os pacientes foram prospectivamente avaliados no pré-operatório e, no mínimo, após 6 meses de pós-operatório. Foram analisados: dados antropométricos, co-mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
2
2
0
1
Order By: Relevance
“…Among the 40 patients, nine had preoperative advanced liver fibrosis; of these, eight (88.9%) were from the public network, responsible for a higher mean BMI than the private one. This is in agreement with the literature, because according to the National Health and Nutrition Examination Survey III, the prevalence of primary non-alcoholic liver disease increases according to the BMI 9 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among the 40 patients, nine had preoperative advanced liver fibrosis; of these, eight (88.9%) were from the public network, responsible for a higher mean BMI than the private one. This is in agreement with the literature, because according to the National Health and Nutrition Examination Survey III, the prevalence of primary non-alcoholic liver disease increases according to the BMI 9 .…”
Section: Discussionsupporting
confidence: 93%
“…Other studies determine the prevalence of non-alcoholic liver disease in patients referred for bariatric surgery. Marceau et al demonstrated prevalence of 86% to steatosis, 23% to steatohepatitis and 2% to cirrhosis among 551 patients 9 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a transient elevation of liver enzymes, which tend to remain high for a period of two to six months after surgery. A significant decrease followed this increase in the period from 10 to 12 months after surgery, maintenance of low levels up to 10 years of surgery 13 , 14 . Thus, our research indicated compliance with the literature data.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, studies have shown reduced hepatic steatosis following bariatric surgery. The possible mechanisms responsible for reducing the incidence of non-alcoholic fatty liver disease in these patients correspond to improved peripheral insulin sensitivity and reduced inflammatory markers 7 , 13 , 14 . Although biochemical concentrations of liver enzymes and their alterations are not considered gold standard for diagnosis and evaluation of hepatic steatosis, many studies use AST and ALT transaminases to evaluate the effect of bariatric surgery on hepatic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A obesidade é considerada o fator de risco mais importante no desenvolvimento de doença hepática não-alcoólica (DHGNA) (Freitas, Freitas, Parolin, Campos, & Coelho, 2007). Segundo Freitas et al (2007), diversos estudos demonstram a prevalência de EH em pacientes com indicação de cirurgia bariátrica, assim como uma pesquisa que apontou prevalência de tal comorbidade em pacientes com obesidade de 76% (Bellentani et al, 2000) e outro estudo que demonstrou prevalência de 86% para esteatose em 551 pacientes obesos (Marceau et al, 1999). No presente estudo 66,7% pacientes submetidos à cirurgia bariátrica apresentavam EH no pré-operatório, sendo 39,3% deles grau III (esteatose grave), 39,3% de grau II (esteatose moderada) e 21,4% de grau I (esteatose leve).…”
Section: Discussionunclassified